A cost‐effective approach to increasing participation in patient‐reported outcomes research in cancer: A randomized trial of video invitations. Issue 4 (21st September 2020) - Signorelli, Christina; Wakefield, Claire E.; McLoone, Jordana K.; Mateos, Marion K.; Aaronson, Neil K.; Lavoipierre, Ange; Cohn, Richard J.; ,
Abstract: Maximizing participation in cancer research is important to improve the validity and generalizability of research findings. We conducted a four‐arm randomized controlled trial to test the impact of a novel video invitation on participant response. We invited childhood cancer survivors and parents of survivors <16 years to complete questionnaires. We compared response rates to an invitation letter (control) vs receiving the letter plus a video invitation on a flash drive presented by a childhood cancer survivor, a pediatric oncologist or a researcher. We explored factors associated with viewing the video and examined the impact of enclosing the USB on study costs. Overall 54% (634/1176) of questionnaires were returned. Participants who received a video invitation on a USB were more likely to return the questionnaire than those who did not (58% vs 47%, P < .001). Participation rate did not significantly differ by video presenter. Forty‐seven percent of participants who received a USB reported watching the video, of whom 48% reported that the video influenced their decision to participate. Participants with a lower income (OR = 0.43, 95% CI = 0.25‐0.74, P = .002) were more likely to report watching the video. Participants who received a video invitation required significantly fewer reminder calls than those who only received a written invitation (mean = 1.6 vs 1.1 calls, P < .001), resulting in a 25% recruitment cost‐saving for the study. Adding a USB with a video study invitation to recruitment packages is a cost‐effective way of improving study participation. This is important in an era of declining study participation and underrepresentation of vulnerable populations in research. Abstract : What's new? High rates of patient participation in cancer research are critical to ensuring that data collected by clinical studies is relevant, reliable, and unbiased. Various recruitment strategies have been developed to improve participation rates, including video invitations. Here, the impact on study participation rates of a USB‐based video invitation sent via mail was examined among childhood cancer survivors who were asked to complete and return a questionnaire. Analyses show that participants who received a video invitation were more likely to return questionnaires than patients who received written information only. The findings offer insight into a cost‐effective approach for maximizing participant recruitment.